"Silicon trade policies" and a comparative analysis of China-U.S. and Japan-U.S. trade conflicts. Issue 1 (2nd January 2020) - Fung, K. C.; Aminian, Nathalie; Fu, Xiaoqing (Maggie); Rhee, Jung Ho; Tung, Chris Y.
ABSTRACT: In this paper, we first compare the U.S.-Japan trade conflicts of the 1980s and 1990s with the current 21st century Trump Administration U.S.-China trade wars. Topics to be compared include complaints of bilateral trade imbalances, 'unique' economic or business organizations and exchange rate manipulations. Relevant contemporaneous research and policy lessons are drawn from the management of previous U.S.-Japan trade disputes and their potential applicability to the ongoing U.S.-China trade rivalry. Since one of the major differences between the periods of the two major trade conflicts is the emergence and prevalence of digital companies, we provide here a formal model of digital firm and see how some ' Silicon trade policies' such as being put on an 'Entity List', being blocked from European technology market and exchange rate depreciation can affect these networked companies.